2012
DOI: 10.1002/jsfa.5644
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis and acetylcholinesterase inhibitory effect of anthocyanin‐rich red leaf tea (cv. Sunrouge)

Abstract: These results suggested that 'Sunrouge' might protect humans from humans from AChE-related diseases by suppressing AChE activity. To obtain sufficient amounts of anthocyanins, catechins and/or caffeine for a functional food material, 'Sunrouge' from the third crop season should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
0
28
1
4
Order By: Relevance
“…EGCG and ECG have previously been shown to produce strong inhibitory effects on lipase activity 1,15 19 . A previous report showed that SR also contained a small amount of EGCG-3-O-methyl 12 . Benifuuki green tea, which contains high levels of EGCG-3-O-methyl, was shown to suppress postprandial hypertriglyceridemia in rats 20 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…EGCG and ECG have previously been shown to produce strong inhibitory effects on lipase activity 1,15 19 . A previous report showed that SR also contained a small amount of EGCG-3-O-methyl 12 . Benifuuki green tea, which contains high levels of EGCG-3-O-methyl, was shown to suppress postprandial hypertriglyceridemia in rats 20 .…”
Section: Discussionmentioning
confidence: 93%
“…SR tea has higher levels of anthocyanins than other more common green tea varieties such as Yabukita YK ; these are effective for the prevention of eyestrain 8 and have antioxidant activity 9 11 . Furthermore, SR also contains similar levels of catechins such as epigallocatechin gallate EGCG as other green tea varieties 12 . On the other hand, green tea leaves including SR have the other useful components such as fat-soluble vitamins.…”
Section: Introductionmentioning
confidence: 98%
“…In accordance with our previous study (13), we determined the levels of two myricetin, five quercetin, and three kaempferol glycosides. With regard to anthocyanins, four delphinidin and four cyaniding glycosides were determined by high-performance liquid chromatography (HPLC), as described in our previous report (15). In addition to these ingredients, catechin, caffeine and amino acid levels in the tea samples were also measured by HPLC, as described in previous reports (16,17).…”
Section: Green Tea Samplesmentioning
confidence: 99%
“…れている嗜好飲料である.茶葉中には, カテキン類, カフェ イン,テアニン,加水分解型タンニン,アントシアニン, 水溶性ビタミン,脂溶性ビタミンなど様々な健康機能性を 有する成分が含まれている 1) .カテキン類は抗酸化作用 2) , 生活習慣病予防作用 3) ∼5) ,免疫賦活作用 6) 7) ,抗アレルギー作 用 8) ∼10) ,抗がん作用 11) 12) ,抗菌作用 13) 14) など,テアニンは α 波 (脳波)の出現頻度の増加作用 15,16) ,脳の神経保護作用 17) ,ス トリクチニンなどの加水分解型タンニンは IgE 産生抑制 作用 18) ,アントシアニンはアセチルコリンエステラーゼ抑 制作用 19…”
Section: 茶は,中国から僧侶により伝えられ,日本で広く親しまunclassified